Effectiveness and safety of bronchodilators and inhaled corticosteroids in the management of chronic obstructive pulmonary disease - Shalabi, Mona Saleh; Aqdi, Sameerah Waheed; Alfort, Odai Ali; Alqattan, Hassan Abdullah; Alotaibi, Fuad Abdulrahman; Faruqui, Afnan Mohammed; Alharbi, Abrar Saleh; Alzahrani, Faisal Fahad; Yahya, Sultan Ahmed; Bakheet, Alaa Abdulrahman; Al Mohammedali, Najeeb Mansour; Al-Ghamdi, Hamed Saeed (International Journal Of Community Medicine And Public Health, 2023)
Chronic obstructive pulmonary disease (COPD) is a lung condition marked by restricted lung airflow. It is a globally prevalent condition affecting almost 300 million individuals. COPD is linked to a significant burden of morbidity and mortality thus necessitating early diagnosis and management. Rising COPD treatment options complicate care and necessitate a review of clinical data to guide treatment choices. Corticosteroids and bronchodilators are the mainstay of treatment for COPD due to their safety and efficacy. Compared to inhaled corticosteroids or long-acting β-agonist therapy alone, inhaled corticosteroids plus long-acting β-agonist lower the risk of exacerbations and enhance lung function and health status in patients with COPD. Patients who experience frequent exacerbations despite taking long-acting bronchodilators and those who have evidence of eosinophilic bronchial inflammation, as shown by high blood eosinophil levels and/or a history of asthma or asthma-COPD overlap, may both benefit greatly from inhaled corticosteroids therapy. Although not widespread, inhaled corticosteroid use is linked to an elevated risk of pneumonia and may vary depending on the particular corticosteroid utilized. Recent research on combination therapy of inhaled corticosteroids and long-acting β-agonist has shown significant advantages and supports its widespread use in COPD patients who experience frequent exacerbations however some clinical studies and trials have also demonstrated quite conflicting outcomes to this therefore necessitating the need for further clinical trials to exhibit conclusive results. The purpose of this research is to review the available information about the effectiveness and safety of bronchodilators and inhaled corticosteroids in the management of COPD.